1995
DOI: 10.1148/radiology.197.3.7480760
|View full text |Cite
|
Sign up to set email alerts
|

Budd-Chiari syndrome: technical, hemodynamic, and clinical results of treatment with transjugular intrahepatic portosystemic shunt.

Abstract: TIPS placement is safe and effective in patients with portal hypertension caused by subacute or chronic BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
12

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 0 publications
0
52
0
12
Order By: Relevance
“…Other recent studies have demonstrated positive results of this new approach in terms of short-term survival. 12,13,26 TIPS is less invasive and therefore probably associated with a lower procedural mortality than PSS. 27 Long-term follow-up studies are needed to assess the place of TIPS in the treatment of BCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies have demonstrated positive results of this new approach in terms of short-term survival. 12,13,26 TIPS is less invasive and therefore probably associated with a lower procedural mortality than PSS. 27 Long-term follow-up studies are needed to assess the place of TIPS in the treatment of BCS.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 Main treatment options include the long-term use of anticoagulants, surgical portosystemic shunting (PSS), 9 -11 transjugular intrahepatic portosystemic shunting (TIPS), 12 and orthotopic liver transplantation. 13 Other treatment methods are thrombolysis 14 and percutaneous hepatic vein balloon angioplasty. 15 Several studies have been published on the cause, clinical manifestations, prognosis, and interventions in BCS.…”
Section: Bcsmentioning
confidence: 99%
“…In the last decade, the use of TIPS in BCS is increasingly described in the world literature [81][82][83][84][85][86][87][88][89][90][91][92][93][94] . In cases with severe liver dysfunction requiring liver transplantation, TIPS used as an interim bridge to transplantation, can improve the situation dramatically [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty with TIPS may be associated splanchnic venous thrombosis, which can be successfully tackled by radiological interventions in the same session [89] . Technical success for TIPS ranges from 75% to 100% in various works [ of TIPS dysfunction (present in 40% to 75% if followed up for more than two years [80,82,84,90,91,93] ) necessitates reinter vention in up to 70% of cases [1,[87][88][89]91] , giving a revision rate of 1.4 revisions per patient [91] . TIPS related complications occur in less than 20% of patients [91] .…”
Section: Discussionmentioning
confidence: 99%
“…A possible radiological intervention in these patients consists of creating a shunt across the portal vein and IVC. With a relatively good midterm outcome, currently TIPS is the preferred intervention for patients having chronic BCS [23][24][25][35][36][37][38][39][40][41] . Creating TIPS in patients having chronic BCS with no available hepatic vein may be technically challenging and difficult and in some cases there may not even be a small notch in the IVC to suggest the site of confluence of hepatic vein and IVC.…”
Section: Transjugular Intrahepatic Portosystemic Shuntmentioning
confidence: 99%